Радіохвилі проти стін: як сигнал wi-fi проходить крізь перешкоди - Шубан, К. Ю. (ХНУРЕ, 2025)
This report is devoted to the analysis of the absorption processes of Wi-Fi signals by obstacles during signal propagation. The important place that Wi-Fi occupies in human life is noted. The influence of walls in household and industrial premises on the level of received Wi-Fi signals is considered. The dependences of the signal attenuation on Wi-Fi frequency range, the absorption capacity of the obstacle substance and other factors are analyzed. Recommendations are given for the optimal choice of the location of the Wi-Fi receiver in the room. The prospects for using Wi-Fi for detecting hidden objects are considered. The possibility of detection a person through a wall is demonstrated. The possibility of detecting a person through a wall is demonstrated.
Keywords: радіохвилі; перешкоди wi-fi сигналу